Diego de la Hoya, aparejador de Juan del Ribeiro Rada - Campos Sánchez-Bordona, María Dolores, 1949- (1996)
The investigation is based on the Architecture of León, in the XVI century, and the personality of Juan del Ribero Rada and his architect's assistant Diego de la Hoya. Both artists stablish an interesting profesional ralitionship. Trough which, Diego de la Hoya will end being in charge of the contruction of Las Carnicerías , the portal of the collegial church of S. Isidoro and other buildings of the town of León.
Keywords: Ribero Rada, Juan del; Hoya, Diego de la; Arquitectura